Evaluation of implementation of fasting guidelines for enterally fed critical care patients. Issue 1 (February 2019) - Jenkins, Bethan; Calder, Philip C.; Marino, Luise V.
Summary: Background & aims: Critically ill adults have increased nutrition risk. Prior to procedures patients are often fasted, leading to nutritional deficits. The use of fasting guidelines may therefore help reduce deficits from accumulating. The aim of this work was to determine the impact on nutrition support delivery following the implementation of fasting guidelines in addition to characterizing staff knowledge of the guidelines. Design: Retrospective data were collected on n = 74 patients at two different time points; prior to launch of fasting guidelines and post launch, with regards to estimated nutritional requirements, nutritional targets, volume of enteral nutrition (EN) delivered and periods of fasting. Clinical variables of interest were collected for up to 14 days. Questionnaires assessing staff knowledge/barriers to usage of the fasting guidelines were administered to ICU staff. Setting: 3 ICUs (General, Cardiac and Neurosciences) within University Hospital Southampton NHS Foundation Trust. Patients: Mechanically ventilated adults in an ICU and receiving exclusive EN. Measurements and main results: Comparison was made between pre- and post-guideline implementation with statistically significant improvements in the % EN delivered (76.4 ± 11.8 vs. 84.1 ± 10.8 (p = 0.0009)) and duration of feeds withheld (41.5 ± 26.6 vs. 27.6 ± 20.8 h (p = 0.02)). There were non-significant improvements pre- and post-implementation in the % of energy and protein delivered (80.7 ± 16.4 vs. 86.5 ± 17.3 (p = 0.15 (NS)); 74 ± 18.3 vs. 79 ± 18.5 (p = 0.15 (NS))). 77% of staff were familiar with the guidelines, whilst 42% requested further education. The main barriers to guideline compliance were delays and unpredictable timing of procedures, and differing guidance from senior staff and non-ICU teams. Conclusions: Implementation of fasting guidelines led to significant improvements in EN delivery and reduced duration of feed breaks. The use of fasting guidelines is a positive step towards increasing nutrition delivery in the ICU. Further staff education and better planning around procedures is required to promote further adherence to the fasting guidelines.